Mrs. Malory and a necessary end [large type] : a Sheila Malory mystery - Holt, Hazel, 1928-2015 (Holt, Hazel, 1928-2015 Sheila Malory mystery., 2013)
Filling in for a friend at a charity shop in the quiet English town of Taviscombe, Sheila Malory is happy for the change of scene and a chance to deal with interesting books, meet new people, and, above all, work for a good cause! Still, not everything in the shop is appealing. The ill-tempered, officious store supervisor, Desmond Barlow, runs the shop as a tyrant. That is, until he's found stabbed to death, and Mrs. Malory puts her impeccable sleuthing into play. Unfortunately, it seems that Desmond was disliked by pretty miuch everyone.